Politica pública, burocracia e instituição: um estudo de caso sobre o Banco do Brasil - Daniete Fernandes Rocha (1995)
The general aim of this study is the analysis of the trajectory of Bank of Brazil, having as inquiry axis the participation of this state agency in the financing of the farming activity of the country. The option for the axis of the agricultural politics is a consequence of the importance of the agricultural credit in the construction of the identity of the Bank, since the constitution of its Section of Agricultural and Industrial Credit - CREAI, in the second half of the decade of 1930, until its intensive participation in the National System of Agricultural Credit - SNCR, from 1965 on. What one seeks is to observe the state and society relation, since the optics of a public agency that, as it will be shown, not only has its action hinged by external interests, but, and mainly, by its proper interests in occupying political-institucional space - acting in its proper name - in the Brazilian society.